Editorial. 30th anniversary of the Revista Argentina de Musicología (1996–2026) (Revista Argentina de Musicología, 2026)
An editorial note briefly outlining the history and significance of the Revista Argentina de Musicología for the history of the institution that publishes it and for the discipline in the country.
Keywords: Editorial; Revista Argentina de Musicología; Review